Representation Of The Evolution Of The Social Function Of Aesthetic Coffee Shop Among Gen Z In Pontianak City - Mutiara; Kayla Andreyani; Mentari (Journal of Creative Power and Ambition (JCPA), 2026)
Aesthetic coffee shops have become popular social spaces for Generation Z in Pontianak. The city was selected as the research site due to Gen Z's high level of enthusiasm for coffee culture and coffee shop visits—activities that have evolved from mere consumption into an integral part of their daily lifestyle. This phenomenon is driven by the rapid emergence of new coffee shops featuring compelling visual and aesthetic concepts, positioning Pontianak as a city with a vibrant "hangout culture" among urban youth. This research aims to analyze the shift in the meaning and social function of coffee shops, moving from places of consumption to spaces for visual expression and the representation of digital identities. Employing a phenomenological approach, the study explores the subjective experiences of Gen Z through observation and in-depth interviews with nine informants—aged 18–24 and comprising students and F&B workers—across six aesthetic coffee shops in Pontianak. The findings reveal that coffee shops function not merely as physical spaces but also as arenas for self-curation, identity performance, and visual production within digital culture. Visual representations circulated via social media create a digital public sphere where curated images supersede direct, lived experiences. Consequently, aesthetic coffee shops have transformed into dual social spaces—simultaneously physical and digital—playing a pivotal role in the construction of Gen Z's identity and existence amidst the dominance of visual culture